COVID-19 Treatment Patterns in Patients with Acute Respiratory Failure at Dr. Hasan Sadikin General Hospital Bandung in 2021–2022 - Rohmawaty, Enny; Sumardi, Aklila Qurrota Aini; Kulsum, Iceu Dimas (Global Medical & Health Communication (GMHC), 2024)
Acute respiratory failure is the most common complication and cause of death in COVID-19 patients. The COVID-19 medication has yet to be discovered. COVID-19 treatment guidelines are constantly being updated. This study aims to determine the COVID-19 treatment patterns in patients with acute respiratory failure at Dr. Hasan Sadikin General Hospital Bandung in 2021–2022. This retrospective, descriptive study used systematic random sampling to examine medical records of COVID-19 patients with acute respiratory failure at Dr. Hasan Sadikin Central General Hospital between June 2021 and June 2022. Gender, age, length of stay, outcome, comorbidities, and pharmacological and non-pharmacological treatment data were analyzed by SPSS software. This study included 120 COVID-19 patients with acute respiratory failure, with the majority of patients are male (55.83%), 30–60 years old (55.83%), length of stay of 1–3 days (52.5%), and have disease severity at severe condition (43.33%) and one comorbidity (37.5%). Patients mostly received non-rebreathing oxygen mask (54.2%), antiviral remdesivir (83.3%), corticosteroid dexamethasone (76.7%), enoxaparin anticoagulants (61.7%), a combination of vitamin C, vitamin D, and multivitamins (45.8%), and two antibiotics (33.3%). Additional treatments include tocilizumab (0.8%), intravenous immunoglobulin (2.5%), and convalescent plasma (0.8%). Statistical analysis shows that patients who stay at the hospital longer, have less or no comorbidities, and are given oxygen therapy have a significant possibility of recovering. Treatments commonly prescribed to COVID-19 patients with acute respiratory failure are antivirals, corticosteroids, anticoagulants, vitamins, and antibiotics, while the administration of oxygen therapy has a significant probability of recovery. DOI: https://doi.org/10.29313/gmhc.v12i3.14073